Hydrological response to land use and land cover changes in a tropical West African catchment (Couffo, Benin) - TOGBEVI, Quentin Fiacre; SINTONDJI, LUC OLIVIER CREPIN (My University, 2021)
This study evaluated the impact of land use and land cover changes on the water balance of the Couffo catchment (Benin) using the Soil and Water Assessment Tool (SWAT). To that end, soil, land uses, hydro-meteorological data including rainfall, temperatures (maximum and minimum), wind speed, solar radiation, relative humidity and discharge data were used as main inputs. To assess the impact of land uses on the catchment water balance, three different land uses (2000, 2006 and 2011) were used. Results showed that from 2000 to 2011, croplands and fallows increased by 34% while the shrub and grass savannahs decreased respectively by 34 and 24%. In addition, agroforestry and gallery forest decreased by 63% and 58% respectively while a rapid increase in settlement. The study outcome suggested that the SWAT provided satisfactory results for discharge with R2, NSE, KGE and absolute percent of bias (absPBIAS) ranged between (0.7–0.9), (0.6–0.9). (0.6–0.9) and (5.3–34) respectively. Moreover, the evaluation of land use and land cover changes on the catchment water balance resulted in an increase in annual surface water and water yield, while the groundwater and actual evapotranspiration (ETa) have decreased. Findings of this study may be a great contribution to water resource management in the Couffo catchment. This may contribute to better allocate water for the actual catchment population demand without dampening those of the future generation.
Keywords: hydrological modelling; land use and land cover; SWAT; water balance; Couffo; catchment; Benin